THE APPLYING OF KWL (KNOW - WANT TO KNOW - LEARNED) STRATEGY IN TEACHING READING COMPREHENSION AT IAIN TAKENGON - Widya Astuti (Journal of Language, Literature and Teaching, 2022)
This research is aimed to describe the applying of K-W-L (Know-Want-Learned) strategy in teaching reading comprehension at IAIN Takengon. The subjects of the study were 30 students of HTN (hukum Tata Negara) class which were at second semester. By using qualitative design, the data were collected through observation, and giving questionnaire. Moreover the researcher administered pre-test and post-test to the students in the way measuring how the KWL strategy brings improvement in students reading comprehension. It was found that the mean score in cycle 1 was increasing, from 50,50 to 75,83  and in cycle II, the mean score was 85,67. Furthermore The result of observation and questionnaire given to students showed that students became more understand about the text read and more enthusiast and the class activity become more fun and enjoyable. Keywords: KWL Strategy,teaching English, reading comprehension.